Amor em tempos de aplicativos: masculinidades heterossexuais e a negociações de afetos na nova economia do desejo - Pelúcio, Larissa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The dissertation aims to expand my ethnography in digital media with men seeking sexual and affective encounters outside of marriage, using specialized websites that promise secrecy and security, as well as adventure and emotion. In that survey. I focused on the Canadian website Ashley Madison. It was a research that sough to think about contemporary conjugalities, but that led to discussions on sexuality and desires, to which were added the negotiations in the field of gender relations, in a scenario market by incitement to adventure and consumption of emotions, leading me to pay attention to the constitution of contemporary masculinities in the face of the demands. To this new key of entry, it was added the enlarged use of applications for smartphones as a resource of insertion in the competitive market of the affections. Therefore, I sough to undestand how heterosexual adult men belonging to the middle and lower middle class have been negotiating sex and love with their potential partners, how they have been dealing with gender relations that cross these contacts in the present, and how, in these digital intermediations, they perform, update and tension models of masculinities. Thus, the main objective of this dissertation was to understand how these communicational resources have influenced the form in which these men, born between 1995, understand and perform their own maculinity, ruled by the logic of romantic consumption, in the sphere of affective capitalism, when they are incited to mobilize specific ways of relationg, not always coherent with those learned in analogic media. Among the findings of this work there is the confirmation of previous reseachers that showed the transposition of vocabulary borrowed from the world of precarious work and intensified consumption to the field of affection. The romantic utopia of the hereosexual pair is confronted with the incitement to... (Complete abstract electronic access below)

Esta tese busca expandir a etnografia realizada em meios digitais com homens que procuravam encontros sexuais e afetivos fora do casamento, utilizando-se para tal de sites especializados que prometiam sigilo e segurança, além de aventura e emoção. Naquela pesquisa, concentrei-me no site canadense Ashley Madison. Tratava-se de pesquisa que buscava pensar as conjugalidades contemporâneas, mas que derivou em discussões sobre sexualiade e desejos, às quais se somaram às negociações no campo das relações de gênero, as quais se davam em cenário marcado pela incitação à aventura e ao consumo de emoções, levando-me a prestar atenção à constituição das masculinidades contemporâneas frente a estas demandas. A esta nova chave de entrada, somou-se o alargamento do uso de aplicativos para smartphones como recurso de inserção no competitivo mercado dos afetos. Busquei, então, na presente pesquisa compreender como homens adultos, que se entendem como heterossexuais, pertencentes à classe média e médica baixa, têm negociado sexo e amor com suas potenciais parcerias e lidado com as relações de gênero que atravessam esses contatos no presente como, nessas intermediações digitais performam, atualizam e tencionam modelos de masculinidades. Assim, o principal objetivo desta tese foi compreender como esses recursos comunicacionais têm incidido na forma desses homens, nascidos entre 1955 e 1985, compreenderem e atualizarem a própria masculinidade, regido pela lógica do consumo romântico, na esfera do capitalismo afetivo, quando são incitados a mobilizar formas de se relacionar específicas, nem sempre coerentes com aquelas que aprenderam nos meios analógicos. Entre achados deste trabalho está a confirmação de teses que mostraram a transposição, para o campo dos afetos, de vocalubário emprestado do mundo do trabalho precarizado e do consumo intensificado... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Relações homem-mulher; Aplicativos móveis; Redes sociais; Masculinidade; Afeto (Psicologia); Amor; Feminismo; Desejo; Mídia digital; Etnologia; Man-woman relationships